Raymond Murray Patterson (1898-1984) - Luste, George J. (ARCTIC, 1991)
R.M. Patterson is recognized by many as one of the finest writers on the Canadian wilderness. While his writing skills earned him a wide and appreciative audience, he was more than a skilled wordsmith. He was also a careful and sympathetic observer, an intrepid explorer and a meticulous historian. Orville Prescott, in the New York Times, described his "Dangerous River as a modest book which betrays no indication that Mr. Patterson realizes what a remarkable man he is." . He published five books over a span of 14 years: Dangerous River (1954), Buffalo Head (1961), Far Pastures (1963), Trail to the Interior (1966) and Finlay's River (1968). .